The accuracy difference between surgical microscope and CBCT to find MB2 canal in mesiobuccal root of maxillary permanent first molar in Malay population - Abdul Majeed, Kais Raad; Mustafa, Nazih Shaban (Czech Society of Prosthetic Dentistry and Czech Dental Chamber Prague, Czech Republic 1st edition, September 2015 ISBN 978-80-260-8581-2, 2015)
Purpose: To investigate the accuracy difference between the surgical microscope and CBCT to find of extra canal MB2 in maxillary first molar among the Malay population. Materials and Methods: This was an in-vitro cross-sectional study on total of 83 extracted maxillary first permanent molars of Malay patients who attended the Polyclinic, Kulliyyah of Dentistry, IIUM. All teeth were cleaned, mounted in a wax box and were sent for a PA radiograph and cone beam computed tomography imaging. Cavity access was performed on all teeth followed by coronal patency under surgical microscope. Results: Out of 83 teeth, 68% were found with MB2 canal. However, prevalence of MB2 canal found in both clinical and radiographic examinations was 68%. Kappa statistic between clinical and radiographic examination was 0.94 (p < 0.001). Conclusions: This study showed that agreement between clinical and radiographic assessments was almost perfect (94%), the treatment can be proceed without expose the patient to extra radiation and it was found the high prevalence of MB2 canal among a sample of Malay population.